The Cost of War: A Comment and a Reply - Charles D. Coleman; Ilona Sologoub (Intereconomics)
Abstract In the July/August issue of Intereconomics, Ilona Sologoub argued that increasing the cost of war would limit the ability of an authoritarian state to wage a war. Here, Charles D. Coleman comments on this statement and offers clarification, followed by a reply from Sologoub.